Validación de la prueba de alfabetización inicial (PAI) en instituciones educativas públicas y privadas pertenencientes a la UGEL No 07. - Bonilla Caviedes, Fiorella Nieves (2013)
This descriptive research with a descriptive design, drawn from a cluster sampling, consisting of 200 5-year-old children from public and private schools belonging to the UGEL No. 07. The Test of Early Literacy Learning – PAI by Malva Villalón and Andrea Rolla which assesses phonological awareness, print awareness, alphabet knowledge, reading and writing, was applied. Within the main results, a reliability coefficient of 0.96 in the overall score was found and intercorrelation coefficients of the other sub tests reached statistically significant values. Additionally, there was a good internal consistency reliability and solid validity indicators to assess harmoniously the 5 key components. Apercentile rank was also carried out for the target population. Key words: Validation, Early literacy, phonological awareness, learning, reading, writing.